THE IMPACT OF SLEEP DEPRIVATION IN ACADEMICS OF MEDICINE IN THE CITY OF BOM JESUS DO ITABAPOANA - de Paula Louvem, Lígia; Ignês Vilela de Andrade Silva, Rubya; Lima Verdan Rangel, Tauã (LINKSCIENCEPLACE, 2026)
The objective of this study is to measure sleep deprivation in medical students in FaculdadeMetropolitana São Carlos in Bom Jesus do Itabapoana and portray this reality, providing the development of measures to solve the problem.This study revisited the literature that consider the students from medicine graduation as a group that has recurring excessive drowsiness daytime and poor-quality of sleepiness interfering negatively in various aspects of their lives. The medical school has a very extensive curriculum, requiring a huge dedication of the students, and they turn out depriving themselves of sleep to supply this need. The study used is a cross-sectional quantitative and descriptive. The instruments used were the literature review and Pittsburgh Sleep Quality Index questionnaire and the Epworth Sleepiness Scale in a sampling of 26 medical students. The quality of sleep has been approached with more emphasis by scholars due to the effects on academic and professional lives of future doctors, caused by interference in the sleep-wake cycle.